Freshwater Turtles & Tortoises of South Asia - Das, Indraneil; Purkayastha, Jayaditya; Sengupta, Saibal (Bhabani Books, 2015)
This book is an identification guide to turtles and tortoises of South Asia. The countries included are Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka. It contains authoritative text, photographs, illustrations, distribution maps, habit and habitat and conservation status of all the turtle species included. lt also contains country-wise checklist of turtle fauna of South Asia.